19F‐NMR Reveals the Role of Mobile Loops in Product and Inhibitor Binding by the São Paulo Metallo‐β‐Lactamase. (2nd March 2017) - Abboud, Martine I.; Hinchliffe, Philip; Brem, Jürgen; Macsics, Robert; Pfeffer, Inga; Makena, Anne; Umland, Klaus‐Daniel; Rydzik, Anna M.; Li, Guo‐Bo; Spencer, James; Claridge, Timothy D. W.; Schofield, Christopher J.
Abstract: Resistance to β‐lactam antibiotics mediated by metallo‐β‐lactamases (MBLs) is a growing problem. We describe the use of protein‐observe 19 F‐NMR (PrOF NMR) to study the dynamics of the São Paulo MBL (SPM‐1) from β‐lactam‐resistant Pseudomonas aeruginosa . Cysteinyl variants on the α3 and L3 regions, which flank the di‐Zn II active site, were selectively 19 F‐labeled using 3‐bromo‐1, 1, 1‐trifluoroacetone. The PrOF NMR results reveal roles for the mobile α3 and L3 regions in the binding of both inhibitors and hydrolyzed β‐lactam products to SPM‐1. These results have implications for the mechanisms and inhibition of MBLs by β‐lactams and non‐β‐lactams and illustrate the utility of PrOF NMR for efficiently analyzing metal chelation, identifying new binding modes, and studying protein binding from a mixture of equilibrating isomers.